Implementation of Pluralist Education at Al-Azhar Mandiri Palu Junior High School - Suryani Lamsu; Askar Askar; Hamlan Hamlan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This thesis examines the Implementation of Pluralist Education at SMP Al-Azhar Mandiri Palu. The school opens for learning opportunities for every student across religions, ethnicities, races and cultures. This school aims to educate all children of the nation, both Muslim and non-Muslim. The research used qualitative method with phenomenological approach. The data were collected through various instruments: observation, interviews and documentation. The sample are a non-Muslim Educator, seven Muslim educators, two Muslim students and six non-Muslim students. Based on the category, all samples played an active role in the application of pluralist education at Al-Azhar Mandiri Junior High School. This study found that pluralist education had been carried out since 1992, with a reference to the school motto of Smart and Moral. It motivates students to be smart but not being arrogant. Non-Muslim students remain in class when Islamic studies take place, and the teacher does not object. The application of Pluralist Education to the students is carried out in the form of growing tasamuh attitude (tolerance), building cooperation in group study and constructing a non-discriminative action based on SARA as well as mutual respect between fellow students.